Analisis Akuntabilitas Pondok Pesantren Arbai Qohar Kabupaten Ngawi - Choirunnisa, Innaki; Habibi, M. Luthfillah (Moderasi : Journal of Islamic Studies, 2023)
This thesis entitled "Analysis of Accountability of the Arbai Qohar Islamic Boarding School, Ngawi Regency" was created with the aim of knowing the process of financial recording at the Arbai Qohar Islamic boarding school and the accountability of the financial reports that have been prepared by the Arbai Qohar Islamic boarding school. This study used a descriptive qualitative analysis method using observation, interview and documentation analysis techniques. The informants in this study were the management, treasurer and also the management of the financial section of the Arbai Qohar Islamic boarding school. In addition, researchers will also look at the archives of financial records from the Arbai Qohar Islamic boarding school. Thus, this research uses primary and secondary data sources. From the results of the analysis conducted by researchers, it can be concluded that the Arbai Qohar Islamic Boarding School in making financial records still uses a manual system, and accountability cannot be fully said. Factors that must be considered in determining accountability are the criteria of accountability itself. Because Islamic boarding schools differ from one another in applying these criteria.